Family Educators' Technology Use and Factors Influencing Technology Acceptance Attitudes. (June 2015) - Walker, Susan K.; Kim, Heeran
<x xml:space="preserve">Abstract</x> The purpose of the study was to examine family educators' use of information and communication technology and factors that predict attitudes favorable to the adoption of technology in practice. Data were obtained from 210 family educators in the United States. Structural equation modeling tested the validity of an adapted Technology Acceptance Model to predict influences on attitudes. Descriptive statistics showed that Internet searching and cell phones were predominantly used both at work and for personal use while social media such as Facebook was used far less for work. Family educators' attitudes toward technology use were directly related to perceived ease of use, perceived usefulness of technology, and subjective norms. Perceived ease of use and perceived usefulness mediated the influence of facilitating conditions (availability of training and assistance) and subjective norms, respectively, on attitudes. Suggestions for research and to support technology integration for family educators are offered.